The Essence of Education: Views of Classical and Contemporary Scholars - Iwantoro Iwantoro; Tobroni Tobroni (Yayasan Letiges Konsultan Sosial, 2024)
This research aims to describe the nature of education according to the thoughts of educational experts in the classical and contemporary eras. Ibnu Miskawaih, Al-Qabisi, and Imam Al Ghozali represent the classical era. At the same time, contemporary-era thinkers will explore the views of Mohammed Arkoun, M. Amin Abdullah, and Fazlur Rahman. This research uses a qualitative approach to the type of library research. The data collection technique uses documentation from written sources/references from books, research results and relevant research journals. The data analysis technique is carried out in data reduction, data presentation, and concluding. The research results state that classical era experts' views regarding the nature of education are how education can form people who are faithful and devout; education should pay attention to the formation of Islamic morals and character. Meanwhile, in the contemporary era, experts see a dichotomy in education. The results of this research provide several solutions to ensure that education does not have dichotomies between religion and science in the world of education, which is differentiated from general education and religious education.